Effects of repetitive transcranial magnetic stimulation on motor function and language ability in cerebral palsy: A systematic review and meta-analysis - Sun, Ying-Ying; Wang, Lei; Peng, Jin-lin; Huang, Yi-jie; Qiao, Fu-qiang; Wang, Pu (Frontiers in Pediatrics, 2023)
Abstract: Objective: This study was conducted to assess the evidence of the quality and the effectiveness of repetitive transcranial magnetic stimulation (rTMS) of motor function and language ability in cerebral palsy (CP). Method: Medline, Cochrane library, Web of Science, Embase, PubMed, and CNKI databases were searched up July 2021 by two independent reviewers. Randomized controlled trials (RCTs) that were published in English and Chinese and met the following criteria were included. The population comprised patients who met the diagnostic criteria for CP. Intervention included the following: rTMS and sham rTMS comparison or rTMS combine with other physical therapy and other physical therapy comparison. Outcomes included motor function, as follows: gross motor function measure (GMFM), Gesell Development Diagnosis Scale, fine motor function measure (FMFM), Peabody developmental motor scale, and Modified Ashworth scale. For language ability, sign-significant relation (S-S) was included. Methodological quality was assessed using the Physiotherapy Evidence Database (PEDro) scale. Results: Finally, 29 studies were included in the meta-analysis. Results of evaluation using the Cochrane Collaborative Network Bias Risk Assessment Scale showed that 19 studies specifically explained the random methods used, among which two studies described allocation concealment, four studies blinded participants and persons and had low risk of bias, and six studies explained that the assessment of outcome measures was blinded. The GMFM of total score was determined by using the random-effect model (I2 = 88%; MD = -1.03; 95% CI [-1.35, -0.71]; P < 0.0001) and FMFM using standardized mean differences (SMDs); P = 0.40 and I2 = 3%. We used a fixed-effect model (SMDs = -0.48, 95% CI [-0.65, -0.30]; P < 0.0001). For language ability, the language improvement rate was determined using a fixed-effect model (P = 0.88 and I2 = 0%; MD = 0.37, 95% CI [0.23, 0.57]; P<0.0001). Conclusion: The rTMS could improve the motor function and language ability of patients with CP. However, rTMS prescriptions varied, and the studies had low sample sizes. Studies using rigorous and standard research designs about prescriptions and large samples are needed to collect sufficient evidence about the effectiveness of using rTMS to treat patients with CP.